The meaning of trust along the treatment pathway of women with breast cancer: a mixed-methods study among cancer survivors - Eleonore Baum; Daniela Bernhardsgrütter; Ramona Engst; Carola Maurer; Jessica Ebneter; Adrienne Zenklusen; Barbara Wartlsteiner; Lotti Barandun; Andrea Neher; Antje Koller; Andrea Kobleder (BMC Women's Health)
Abstract Purpose Women with breast cancer face a high degree of uncertainty. Trust between health providers and patients has been shown to improve patient quality of life and may enhance clinical outcomes. This study aimed to explore the meaning of trust along the treatment pathway. Methods The study followed a convergent mixed-methods design. We collected qualitative data longitudinally from diagnosis to follow-up using unstructured digital diaries and 45 semi-structured interviews with twelve women with breast cancer. To measure symptom burden and trust, we collected quantitative data by means of 57 questionnaires. Data analysis was based on phenomenology according to van Manen and on descriptive statistics. Data synthesis resulted in a conceptual model of trust. Results The women experienced trust as a dynamic phenomenon within the biomedical cancer care “machinery”. Their trust was strongly influenced by contextual factors, professionals’ expertise, and person-centeredness. The relevance of trust differed according to treatment phases. Conclusions Due to a high degree of uncertainty, trust was particularly important. Professionals positively influenced the women’s trust to a certain extent through a patient-centered approach and by demonstrating expertise within the biomedical cancer care “machinery”. The conceptual model of trust should receive attention to bring care closer to the women’s lived experience so that their care experience can be improved.